Epidemiology of Ocular Manifestations in Autoimmune Disease - Glover, Katie; Mishra, Deepakkumar; Singh, Thakur Raghu Raj (Frontiers in Immunology, 2021)
The global prevalence of autoimmune diseases is increasing. As a result, ocular complications, ranging from minor symptoms to sight-threatening scenarios, associated with autoimmune diseases have also risen. These ocular manifestations can result from the disease itself or treatments used to combat the primary autoimmune disease. This review provides detailed insights into the epidemiological factors affecting the increasing prevalence of ocular complications associated with several autoimmune disorders.